Strategi Komunikasi Pemasarasan dalam Kegiatan Event CV. Siki Coffee - Airlangga Aditya Dwi Prasojo; Wiki Angga Wiksana (Bandung Conference Series: Communication Management, 2024)
Abstract. A communication strategy is a plan for conveying messages by combining various communication elements (such as frequency, form, content, and communication channels) so that messages sent are more easily received and understandable, and can change attitudes or behavior in accordance with the purpose of communication. According to Kulvisaechana, the use of a combination of communication facets includes the frequency of communication, the formality of communication, the content of communication, and the channels of communication. Based on the research background, the researcher will focus on research and problems in marketing communication strategies in event activities. The data analysis technique used in this study is to use the marketing communication strategy Shrivastava & Dawle, to find out the marketing communication strategy carried out by CV. Siki Coffee in the event activities that followed. This research is motivated by facts about CV. Siki Coffee which utilizes event activities to be used as a promotional media for its products. Data collection techniques are carried out by conducting interviews, observation, and documentation. Abstrak. Strategi komunikasi adalah rencana pengutaraan pesan dengan menggabungkan berbagai elemen komunikasi (seperti frekuensi, bentuk, isi, dan saluran komunikasi) agar pesan yang dikirimkan lebih mudah diterima dan dapat dipahami, serta dapat merubah sikap atau perilaku sesuai dengan tujuan komunikasi. Menurut Kulvisaechana penggunaan kombinasi faset-faset komunikasi dimana termasuk di dalamnya frekuensi komunikasi, formalitas komunikasi, isi komunikasi, dan saluran komunikasi. Berdasarkan latar belakang penelitian, maka peneliti akan memusatkan penelitian dan permasalahan dalam strategi komunikasi pemasaran dalam kegiatan event. Teknik analisis data yang digunakan dalam penelitian ini adalah dengan menggunakan strategi komunikasi pemasaran Shrivastava & Dawle, untuk mengetahui strategi komunikasi pemasaran yang di lakukan CV. Siki Coffee dalam kegiatan event yang diikuti. Penelitian ini dilatarbelakangi oleh fakta tenteng CV. Siki Coffee yang memanfaatkan kegiatan event untuk dijadikan media promosi prodaknya. Tehnik pengumpulan data yang dilakukan yaitu dengan melakukan wawancara, observasi, dan dokumentasi.